2016
DOI: 10.1016/j.ophtha.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Plus Disease in Retinopathy of Prematurity

Abstract: Objective To determine expert agreement on relative retinopathy of prematurity (ROP) disease severity, whether computer-based image analysis can model relative disease severity, and to propose consideration of a more continuous severity score for ROP. Design We developed two databases of clinical images of varying disease severity (100 images and 34 images) as part of the i-ROP (Imaging and Informatics in ROP) cohort study and recruited both expert physician, non-expert physician, and non-physician graders t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 68 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The smaller dataset was a fully independent dataset that has been well characterized by multiple expert classifications in prior work. 18 20 It is included in this study to present the performance of our system on previously studied dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The smaller dataset was a fully independent dataset that has been well characterized by multiple expert classifications in prior work. 18 20 It is included in this study to present the performance of our system on previously studied dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Experts have poor absolute agreement on ROP vascular disease classification (normal, plus, or pre-plus) but good relative agreement on ROP disease severity. 33 As previously described, this finding motivated the development of a continuous vascular severity score using the i-ROP DL system. This continuous ROP vascular score provided a more quantitative diagnosis for plus disease and was associated with both the ICROP category of disease at a single point in time and clinical progression of ROP over time.…”
Section: Recommendations For Future Research In Ai Applied To Ropmentioning
confidence: 64%
“…Vascular disease in ROP presents on a continuum, as shown in Figure 2 , and experts have been shown to have poor absolute agreement on classification (normal, plus, or pre-plus), but good relative agreement on disease severity. 33 This finding motivated the development of a continuous vascular severity score using the i-ROP DL system. Redd et al reported that a scale from 1 to 9 could accurately detect type 1 ROP with an area under the curve of 0.95 and, in theory, could decrease the number of ophthalmoscopic examinations by 80% in a real-world telemedicine program because most babies will have no or mild disease.…”
Section: A Continuous Severity Score For Ropmentioning
confidence: 99%
“…Intergrader variation in the diagnosis of plus disease has been well documented in the literature, 48 50 and may be attributable to grader-specific biases to undercall or overcall pre-plus and plus disease. 51 , 52 This can also apply to a single clinician who determined the plus disease at the bedside (our gold standard). The relatively low intergrader agreement for plus, pre-plus, or neither grades may therefore be due not to limitations of the RVSV-OCT montages themselves, but to unique disease thresholds for each grader, despite the existence of standardized grading criteria.…”
Section: Discussionmentioning
confidence: 99%